Comparative Analysis of the Health Level of State-Owned Banks with Private Banks - Dwi Ayu Wulan Iswari; Sugiharti Binastuti (Universitas Gunadarma, 2024)
This research employs the Risk-Based Bank Rating (RBBR) approach to assess the financial health of state-owned and private banks. The significance of this study lies in the increasing necessity for a comprehensive evaluation methodology to assess bank performance in a competitive financial market. The research objectives are twofold: firstly, to compare the health levels of state-owned and private banks and secondly, to identify any significant differences. The methods used include the analysis of risk profile, GCG, earnings, and capital during the 2020-2023 period. The findings show that there are no significant differences between state-owned and private banks based on these criteria. These results highlight the competitiveness of both bank types and provide insights into their performance stability in the banking sector.